From globalization to global history: toward another representation of the contemporary world (2007)
The core thesis of the article deals with the way in which deep transformations of our contemporary world have generated incertitude in the classic epistemological basis of social sciences. To show that, the author briefly examines the main problems of our contemporary times in a procedure that denotes a gap between reality and thought. Then, the article focuses on the reasons leading to positioning the concept of globalization as an axis around which the contemporary reality has been intendedly decoded. Finally, the author proposes a new way to make contemporary reality apprehensible through the concept of global history.